Communication theory for everybody a handbook - Henson, Mari J. (Giraffe Books, 2004)
Contents: Definitions and theories of communication. Aspects of communication. Kinds and styles of communication. Applications. Glossary. Recommended readings. Selected titles from Giraffe Books.